Alcohol use, psychological distress, and subjective well-being among young adult university students: A cross-national study between Serbia and Italy. Issue 4 (2nd October 2019) - Piumatti, Giovanni; Lietz, Francesco; Aresi, Giovanni; Bjegovic-Mikanovic, Vesna
ABSTRACT: Few studies have cross-nationally tested the mediators of the relationship between alcohol use and subjective well-being among university students. This study examined how self-reported psychological distress symptoms mediate the association between alcohol use (drinking frequency and binge-drinking frequency) and subjective well-being among 637 Serbian and 705 Italian university students. Psychological distress mediated the negative relationship between binge-drinking frequency and subjective well-being among Serbians (partial mediation) and Italians (full mediation). Drinking frequency was not associated with psychological distress or subjective well-being. Binge drinking may negatively affect subjective well-being among university students by enhancing symptoms of psychological distress.